Learning From Human Responses to Deconditioning Environments: Improved Understanding of the “Use It or Lose It” Principle - Hart, David A. (Frontiers in Sports and Active Living, 2021)
Physical activity and mobility are intrinsic to the functioning of Homo sapiens, and required for maintenance of health. Thus, systems such as the cardiovascular (CV) and musculoskeletal (MSK) systems appear to require constant reinforcement or conditioning to maintain integrity. Loss of conditioning and development of deconditioning can have multiple consequences. The study of different types of deconditioning and their prevention or reversal could offer a number of clues to the regulation of these systems and point to how deconditioning poses risk for disease development and progression. From detailed study of deconditioning associated with spaceflight, a condition not predicted by evolution, and prolonged bedrest, the genetic and molecular findings could provide an insightful background to better understand human heterogeneity and how exercise may impact the risks associated with chronic deconditioning. The effectiveness of optimized exercise protocols likely depend on the nature of the deconditioning, the individual, whether one is addressing prevention of deconditioning-associated disease or the progression of such conditions, and whether it is focused on acute or chronic deconditioning. Based on the chronic deconditioning associated with prolonged bedrest and space flight, and the limitations on the reversal of such changes, elaboration of more details could provide new insights into the regulation of systems such as the CV and MSK systems and may lead to improved protocols in addition to exercise to prevent loss of system integrity during senescence/aging. Exercise across the lifespan may interfere with such age-related declines in system integrity but may not be sufficient on its own.